2008
DOI: 10.1057/omj.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Mood, emotion, and affect in group performance: an experiential exercise

Abstract: One path to the successful transference of knowledge is through linking concepts to students' experience. To provide this connection, we used an experiential methodology to design an exercise called mood, emotion, and affect in group performance. This exercise provides learners with an opportunity to experience, in addition to hearing and reading about, the effects of positive and negative dispositions on a group task. We describe the design and mechanics of the exercise with practical reflections from the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There is also evidence suggesting that people's ability to recognize and reflect on their own emotions and their capacity to empathize with others' emotions play an important role in their interpersonal relationships at work (Matthews, Zeidner, & Roberts, 2002;Salovey & Mayer, 1990). In addition, recent studies on management education demonstrated that analyzing and discussing work-related emotions in classroom settings can help students gain a better understanding of the dynamics of social interactions in organizational life (Chavez & Méndez, 2008;Gibson, 2006).…”
Section: Cross-cultural Communication Business Education and Emotionsmentioning
confidence: 99%
“…There is also evidence suggesting that people's ability to recognize and reflect on their own emotions and their capacity to empathize with others' emotions play an important role in their interpersonal relationships at work (Matthews, Zeidner, & Roberts, 2002;Salovey & Mayer, 1990). In addition, recent studies on management education demonstrated that analyzing and discussing work-related emotions in classroom settings can help students gain a better understanding of the dynamics of social interactions in organizational life (Chavez & Méndez, 2008;Gibson, 2006).…”
Section: Cross-cultural Communication Business Education and Emotionsmentioning
confidence: 99%
“…First, from our perspective and as already delineated, on the basis of literature that, mood is nonstimulus specific (Batson et al, 1992;Chavez & Méndez, 2008;McGeer & McGeer, 1980) and is relatively lasting emotional state (Morgan et al, 1993). Given these properties of mood, it implies that the organization and managers may not be able to exert significant control on an employees' mood-state.…”
Section: Implications and Conclusion For Hrdmentioning
confidence: 87%
“…Thus, mood is a relatively lasting emotional state (Morgan, King, Weisz, & Schopler, 1993) and differs from emotion in the sense that, mood is less specific, less intense, and less likely to be triggered by a particular stimulus or event (Batson, Shaw, & Oleson, 1992; Chavez & Méndez, 2008; McGeer & McGeer, 1980). Like emotion, mood is also an affective state (Baas et al, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work context, researchers found relations between mood and performance (Chavez and Mendez, 2008;Coulson et al, 2008), organisational spontaneity (George and Brief, 1992), prosocial behaviour at work (George, 1991), employee withdrawal behaviour (Andrew et al, 2005), and creativity in the workplace (George and Zhou, 2007).…”
Section: Moodmentioning
confidence: 99%